2015
DOI: 10.1101/gr.193433.115
|View full text |Cite
|
Sign up to set email alerts
|

SCRaMbLE generates designed combinatorial stochastic diversity in synthetic chromosomes

Abstract: Synthetic chromosome rearrangement and modification by loxP-mediated evolution (SCRaMbLE) generates combinatorial genomic diversity through rearrangements at designed recombinase sites. We applied SCRaMbLE to yeast synthetic chromosome arm synIXR (43 recombinase sites) and then used a computational pipeline to infer or unscramble the sequence of recombinations that created the observed genomes. Deep sequencing of 64 synIXR SCRaMbLE strains revealed 156 deletions, 89 inversions, 94 duplications, and 55 addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
162
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 136 publications
(170 citation statements)
references
References 35 publications
7
162
1
Order By: Relevance
“…The SCRaMbLE system was designed to permit on-the-fly genome rearrangements leading to a combinatorially diverse population of cells with a corresponding selectable phenotypic diversity. Consistent with design goals, strains generated by SCRaMbLE with the circular synIXR chromosome led to inversions and deletions at the designed sites, including minimized versions of synIXR, with no changes to the nonsynthetic chromosomes (20). A large number of strains also contained duplications, providing additional useful variation to evolve new phenotypes.…”
Section: Loxpsym Sites Enabling Scramblementioning
confidence: 75%
“…The SCRaMbLE system was designed to permit on-the-fly genome rearrangements leading to a combinatorially diverse population of cells with a corresponding selectable phenotypic diversity. Consistent with design goals, strains generated by SCRaMbLE with the circular synIXR chromosome led to inversions and deletions at the designed sites, including minimized versions of synIXR, with no changes to the nonsynthetic chromosomes (20). A large number of strains also contained duplications, providing additional useful variation to evolve new phenotypes.…”
Section: Loxpsym Sites Enabling Scramblementioning
confidence: 75%
“…For example, tRNA genes were deleted during the design of Sc2.0 chromosomes, to be relocated to a separate “neochromosome” (13), and subtelomeric regions were substantially altered as well, with large repeated sequences corresponding either to Y′ or gene families deleted. Further, loxPsym sites encoded by Sc2.0 chromosomes enable inducible evolution by SCRaMbLE (synthetic chromosome rearrangement and modification by loxP -mediated evolution) (14, 15) to generate combinatorial genomic diversity through rearrangements (16). Several synthetic chromosomes are now built (14, 1722); it is thus possible to experimentally address whether or not Sc2.0 modifications affect the overall chromosome organization in strains carrying synthetic chromosomes.…”
mentioning
confidence: 99%
“…(iv) Upon completion, the synthetic chromosome can either be exploited in yeast, to address specific questions of interest, or the synthetic region can also be isolated and transferred into the genome of another organism (n: nucleus). positioned along the right arm of the synthetic chromosome IX showed that, in addition to the relatively simple rearrangements mentioned above, complex structures could be observed [22]. Interestingly, the frequencies of recombination events between distant loxP sites followed the collision frequencies expected from DNA looping theoretical models.…”
Section: Examples Of Applicationsmentioning
confidence: 77%